Stock Prices, News, and Business Conditions - McQueen, Grant; Roley, V. Vance (Review of Financial Studies, 1993)
Previous research finds that fundamental macroeconomic news has little effect on stock prices. We show that after allowing for different stages of the business cycle, a stronger relationship between stock prices and news is evident. In addition to stock prices, we examine the effect of real activity news on proxies for expected cash flows and equity discount rates. We find that when the economy is strong the stock market responds negatively to news about higher real economic activity. This negative relation is caused by the larger increase in discount rates relative to expected cash flows.